Lipid rafts as functional heterogeneity in cell membranes. (21st September 2009) - Lingwood, Daniel; Kaiser, Hermann-Josef; Levental, Ilya; Simons, Kai
Abstract : Biological membranes are not structurally passive solvents of amphipathic proteins and lipids. Rather, it appears their constituents have evolved intrinsic characteristics that make homogeneous distribution of components unlikely. As a case in point, the concept of lipid rafts has received considerable attention from biologists and biophysicists since the formalization of the hypothesis more than 10 years ago. Today, it is clear that sphingolipid and cholesterol can self-associate into micron-scaled phases in model membranes and that these lipids are involved in the formation of highly dynamic nanoscale heterogeneity in the plasma membrane of living cells. However, it remains unclear whether these entities are manifestations of the same principle. A powerful means by which the molecular organization of rafts can be assessed is through analysis of their functionalized condition. Raft heterogeneity can be activated to coalesce and laterally reorganize/stabilize bioactivity in cell membranes. Evaluation of this property suggests that functional raft heterogeneity arises through principles of lipid-driven phase segregation coupled to additional chemical specificities, probably involving proteins.